Adherence characteristics of attaching and effacing strains of Escherichia coli from rabbits. - Robins-Browne, R M (1994)
Twelve strains of Escherichia coli previously reported to cause diarrhea in rabbits were examined for properties associated with virulence. Ten strains met the criteria for classification as enteropathogenic E. coli in that they were diarrheagenic strains that evoked attaching-effacing lesions in the small intestine and did not produce detectable enterotoxins or cytotoxins. These bacteria exhibited a variety of patterns when investigated for adherence to HEp-2 epithelial cells. Although several strains displayed localized and/or diffuse adherence to epithelial cells, they did not hybridize with DNA probes that recognize the genes responsible for these phenotypes in diarrheagenic E. coli from humans. The bacteria also varied in their ability to bind to erythrocytes and intestinal brush borders from various animal species. Six strains adhered to rabbit brush borders; two of these also adhered to brush borders from other animals. Two strains that did not adhere to rabbit brush borders adhered to those from guinea pigs or sheep. Only one of the strains investigated carried AF/R1 fimbriae, which are believed to govern the host specificity of this category of diarrheagenic E. coli. This strain was E. coli RDEC-1, which remains the only E. coli strain to date that is known to carry fimbriae of this type. The results indicate that although diarrheagenic E. coli strains from rabbits may have common properties associated with the ability to produce attaching-effacing lesions, they differ from each other and from enteropathogenic E. coli of humans in terms of some of the adhesins that mediate binding to eukaryotic cells.